Numerical Study On The Effectiveness Of Homogeneous Multiphase Volume Of Fluid (VOF) Model In Rubber Processing - Lee, Eyann (Universiti Sains Malaysia, 2022)
Numerical simulation has been widely used in simulation of polymer processing. The use of simulation in injection moulding was able to detect potential defects which could help to reduce the cost and time wasted. The purpose of this thesis was to study the effectiveness of homogeneous multiphase Volume of Fluid (VOF) model in rubber processing. To run the simulation, the governing equations, Cross and Carreau models were used. The mould model was taken from a established research paper. Validation of Ansys Fluent was first conducted by comparing the experimental and simulation results from the research paper. Then, the mould filling behaviour and effectiveness of rheology models were evaluated. Next, the mould was modified to investigate the mould filling behaviour of natural rubber in mould with different geometry such as addition of melt traps and implementation of obstacles. Ansys Fluent showed good agreement with the experimental results from the research paper and the Cross model showed better accuracy than the Carreau model. During mould filling, the natural rubber tended to flow into cavity with larger thickness and the rate of flow of natural rubber was affected by the inlet speed or injection speed. Besides that, the implementation of melt trap was able to trap the high viscosity melt front of the flow. Moreover, the presence of obstacles in the mould affected the formation of flow line defects and maybe caused short shot. In conclusion, the use of VOF model with Cross model in Ansys Fluent was a suitable model to predict the flow behaviour of natural rubber.